Performance-Based Financing tool for local level sustainable enterprise finance in community forestry - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
ICRAF Dryad Cameroon Field Monitoring System (FMS) is now operational in all 32 CFEs with all communities fully trained- including 179 employees (40% women and 60% Men); A paper on “the state of community forest enterprises (CFEs as successful social enterprises: empirical evidence from Cameroon”